Retaining committed customers for a consumer bank: A study across search-experience-credence products - May, Chia-Yun (2005)
Researchers have discussed relational bonds that enhance customer commitment in different industries; however few of them specifically focus on the consumer-banking sector. In order to fill the gap, the study aims to investigate the impact of the three levels of the relational bonds; financial, social and structural on the high-income segment's commitment in the Taiwan market across consumer-banking products/services, which were categorized into search, experience and credence (SEC) products/services.